Battlefield forensics for Persian Gulf States regional and U.S. military weapons, ammunition and headstamp markings - Mikko, Don; Bailey, William S. (William Scherer) (CRC Press, Taylor & Francis Group, 2019)
Battlefield Forensics for Persian Gulf States provides an illustrative reference of various weapons, toolmarks, headstamps, and other traits in order to identify the origins of a variety of guns, casings, and ammunition that can be found in the Middle East.